A Landmark Crime of Poisoning - Meledandri, Giovanni (British Journal of Healthcare and Medical Research, 2024)
The account of Germanicus' death plays out in Roman history as a true detective story. The affair contains more than one mysterious aspect and only through the words of the historians who have handed down the story is it possible to propose an interpretation of what happened. The paper proposes a critical, textual medical and legal analysis of the ancient sources aimed at formulating a contextualized hypothesis on poisoning as the most likely cause of Germanicus' sudden death, thus eliminating him from succession to the Roman Empire and paving the way for Caligula. Julius Caesar Germanicus died on Oct. 10th 19 C.E., in Epidaphne near Antioch of Syria, under mysterious circumstances, at the age of 33, during the Principate of Tiberius. He himself invoked poisoning. The results of the analysis supported the venom hypothesis, which is basically recognized and endorsed by all the four quoted authors. In conclusion, the hypothesis that Germanicus fell victim to a criminal plot that used the crime of poisoning to exclude him from the succession looks to be textually supported.